1992
DOI: 10.1161/01.hyp.19.1_suppl.i36
|View full text |Cite
|
Sign up to set email alerts
|

The immune system and hypertension.

Abstract: Primary or secondary activation of immune mechanisms has been implicated in the pathogenesis of many forms of hypertension. Changes in serum immunoglobulin levels, alterations in both humoral and cellular immune functions, and inherited abnormalities of the complement system have been identified in patients with essential hypertension. In addition, many models of spontaneous hypertension (such as the Okamoto and Lyon strains of hypertensive rats and the hypertensive New Zealand Black mouse) have identifiable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
43
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 0 publications
4
43
1
Order By: Relevance
“…5,6 Some reports 3,4,7 have shown a significant association between inflammatory markers and elevated BP, consistent with our findings. Kim et al 8 reported that TNF-a level correlated with the BP index and IL-6 level correlated with the BP variability index, implying that inflammation may be a mediator for the link between BP variability and target organ damage.…”
Section: Discussionsupporting
confidence: 92%
“…5,6 Some reports 3,4,7 have shown a significant association between inflammatory markers and elevated BP, consistent with our findings. Kim et al 8 reported that TNF-a level correlated with the BP index and IL-6 level correlated with the BP variability index, implying that inflammation may be a mediator for the link between BP variability and target organ damage.…”
Section: Discussionsupporting
confidence: 92%
“…The immune imbalance status correction in SHR delayed the development of hypertension (31) and therefore the immunological dysfunction is one of the etiological agent of hypertension (32). An alteration in the serum immunoglobulin levels was detected in both animals and patients, demonstrating an inflammatory involvement in hypertension (33). Furthermore, in hypertensive subjects, an increased interaction between inflammatory cells and endothelial cells (34) was demonstrated.…”
Section: Discussionmentioning
confidence: 89%
“…The immune system, especially autoantibodies with agonistlike activity, plays important roles in the hypertension (1,2). Autoantibodies against the α 1 -adrenoceptor with agonist-like activity had been found in patients with malignant hypertension, primary hypertension and refractory hypertension (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%